A Decade of Trauma, Grievance, and Resiliency: The Testimonial Narratives of the Victims of 2009 Ondoy Flood Disaster in Marikina City, Philippines - Christien Tugano, Axle (International Journal of Transdisciplinary Knowledge, 2022)
This study is written as a commemoration to a decade of reminiscence of the 2009 tragedy brought by Typhoon Ondoy in Marikina City, Philippines. This study focuses on the testimonies and personal experiences of distinct residents of the local communities or barangays of Tumana, Malanday, and Nangka. This study wants to bring out the trauma, grievance, and resiliency of Marikina residents during times of disaster and calamities. The interviewed people will provide narratives of their trauma, grievance, and resiliency. As disclaimer, the study does not focus on what the local government has to say on the perspectives of their constituents on the said three aspects of this study. Instead, the study is meant to show how selected victims look at the steps taken by their local government in order to provide safety and security to the community.